Semi-mechanistic population pharmacokinetic model incorporating glutathione S-transferase activity for personalized busulfan dosing in pediatric allogeneic hematopoietic cell transplantation - Cao, Di; Qian, Xiaowen; Wang, Ping; Zheng, Xinyi; Huang, Shan; Wei, Zhonglin; Jiang, Wenjin; Yu, Ling; Jiang, Xin; Yu, Ying; Mao, Junjun; Zhai, Xiaowen (Frontiers in Pharmacology, 2025)
BackgroundBusulfan is known for its high inter- and intra-individual pharmacokinetics/pharmacodynamics (PK/PD) variability, especially in children. Therefore, we aimed to identify factors affecting PK variability of busulfan in pediatric allogeneic hematopoietic cell transplantation (HCT) recipients and investigate the effect of glutathione S-transferase (GST) activity on busulfan metabolism using a semi-mechanistic population PK model.MethodsOverall, 636 whole-blood busulfan concentrations from 65 pediatric HCT recipients were analyzed using nonlinear mixed-effects modeling. A semi-mechanistic population PK model was developed to describe busulfan metabolism in response to glutathione (GSH) depletion. The effects of potential covariates were selected based on previous study and physiologically-based theoretical mechanisms. Virtual clinical trials were conducted to compare different dosing strategies, and model-based optimal dosing regimen was recommended.ResultsA two-compartment model with first-order absorption was selected to describe busulfan PK. A GSH compartment was added to represent the relative amount of GSH available at any time. The estimated mean clearance of busulfan was 9.57 L h−1 (relative standard error: 10.8%). Busulfan disposition was best described by including normal fat mass (NFM) allometrically and GST enzyme activity on SGSH exponentially. The SGSH increased by 40.6% as GST enzyme activity increased from 0.9 nmol/min/mL to 20.7 nmol/min/mL. Patients with weights (WT) of 9–16 kg are at high risk of sinusoidal obstructive syndrome (SOS) when receiving WT-based dosing strategy.ConclusionNFM, age-dependent maturation function, and GST enzyme activity may contribute to busulfan PK variability. The WT-based dosing strategy showed a higher risk of SOS than the age-based dosing strategy in 9–16 kg patients.